PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION KARYAWAN FAJAR TOSERBA TALAGA - Jaenal Hak, Muhammad Rapi; Fitriani, Lili Karmela; Arraniri, Iqbal (Universitas Kuningan, 2024)
The problem in this research is the Employee Turnover Intention at Fajar Toserba Talaga which is still not optimal. The purpose of this study was to determine the effect of workload and compensation both partially and simultaneously on employee turnover intention at Fajar Toserba Talaga. The method used in this study is a quantitative method. The population is all employees of Fajar Toserba Talaga totaling 51 employees. The conclusions from the results of this study are: (1) Workload and compensation simultaneously have an influence on employee turnover intention. (2) Workload has an effect on employee turnover intention, (3) Compensation has no effect on employee turnover intention.